Parental warmth, adolescent emotion regulation, and adolescents’ mental health during the COVID-19 pandemic - Boullion, AnnaMaria; Linde-Krieger, Linnea B.; Doan, Stacey N.; Yates, Tuppett M. (Frontiers in Psychology, 2023)
The United States (U.S.) Surgeon General Advisory has characterized the COVID-19 pandemic as a youth mental health crisis. Thus, elucidating factors affecting adolescents' mental health during the pandemic is important for supporting youth through current and future challenges. Parenting influences adolescents' ability to cope with stressors, and emotion regulation strategy use may underlie these effects.Methods: This longitudinal study of 206 adolescents (49% female; 46.6% Latine) from the U.S. evaluated pathways from perceived parental warmth and affection at age 12 to changes in adolescents' internalizing and externalizing problems from before the pandemic (age 14) to the initial phase of the US COVID-19 pandemic in Spring 2020 (age 15) through adolescents' prepandemic cognitive reappraisal and expressive suppression emotion regulation strategy use at age 14.Results: Parental warmth and affection predicted decreased internalizing, but not externalizing, problems during the initial phase of the pandemic, and this effect was explained by adolescents' reduced reliance on expressive suppression as an emotion regulation strategy.These findings illuminate parenting and emotion regulation strategy selection as modifiable processes to support adolescents' mental health in this crisis and beyond.